A tantalum-doped hafnium-based oxyhalide solid-state electrolyte, a preparation method and applications
Patent Information
- Application Number
- CN202611018946.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-27
AI Technical Summary
但现有方案多集中于宽泛通式、元素并列列举、卤素组成调节或通用氧引入路线;对于以Hf为主体金属中心、以Ta为高价掺杂组分,并同时包含Cl-和O2-混合阴离子骨架的Li-Hf-Ta-Cl-O卤氧化物体系,现有技术仍缺少针对性的材料组成设计和可重复制备方案
(1)通过Ta5+调控Hf基Cl/O混合阴离子骨架,提升锂离子传导性能
Smart Images

Figure CN122992159A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state battery technology, specifically relating to a tantalum-doped hafnium-based halide oxide solid electrolyte, its preparation method, and its application. Background Technology
[0002] With the rapid development of electric transportation, portable electronic devices, and large-scale energy storage systems, the requirements for energy density, safety, and cycle life of lithium-ion batteries are constantly increasing. Existing commercial lithium-ion batteries typically use organic liquid electrolytes, which pose risks of leakage, combustion, and thermal runaway under conditions such as high temperature, overcharging, mechanical damage, or internal short circuits, making it difficult to fully meet the development demands of high-safety and high-energy-density energy storage systems. All-solid-state lithium-ion batteries, by replacing liquid electrolytes with solid electrolytes, can reduce the safety hazards caused by electrolyte flammability and leakage, and provide an important material foundation for the construction of high-voltage cathodes, lithium metal anodes, and high-energy-density battery systems.
[0003] In all-solid-state lithium-ion battery systems, the solid electrolyte conducts lithium ions between the positive and negative electrodes. Its ionic conductivity, interfacial contact performance, and chemical stability affect the battery's rate performance, cycle stability, and safety. Existing solid electrolytes mainly include oxide, sulfide, polymer, and halide systems. Oxide solid electrolytes typically possess good thermal and electrochemical stability, but they often require high-temperature sintering for preparation and exhibit poor solid-solid interfacial contact with the electrode materials. Sulfide solid electrolytes offer high room-temperature ionic conductivity and good formability, but are sensitive to air and moisture, requiring stringent environmental conditions for storage and preparation. Polymer solid electrolytes offer good processing performance, but their room-temperature ionic conductivity and high-voltage stability often fail to meet the demands of high-energy-density batteries.
[0004] Halide solid electrolytes exhibit good oxidation stability and compatibility with high-voltage cathode materials, and their ion conductivity can be improved through metal element selection, halogen composition adjustment, and heterovalent doping. Existing publicly available technologies have made significant strides in the field of halide solid electrolytes. For example, CN112204675B discloses a halide solid electrolyte with the general formula Li... 6-4a M a The X6 halide solid electrolyte material, where M can be selected from at least one of Zr, Hf, and Ti, and X is a halogen element, indicates that group IVB metal centers have been used in the composition design of halide solid electrolytes. Furthermore, CN115732751A discloses a material with the chemical formula Li... a M b Y' 1-b X c Cl a+4-b-cA halide solid electrolyte material is proposed, in which Y' can be selected from group IVB elements such as Hf, Zr and Ti, and the ion transport performance is improved by adjusting the metal element and halogen composition.
[0005] In the design of heterovalent doped electrolytes, existing technologies have incorporated elements such as Hf, Zr, Ta, and Nb into a relatively broad range of halide solid-state electrolyte designs. For example, CN118073640B discloses a doped halide solid-state electrolyte and its preparation method, aiming to improve ionic conductivity by adjusting the lithium-ion migration environment through different combinations of metal ions of different valence states and doping. CN119487582A further discloses a doped solid-state electrolyte containing A and M... α M β M γ A solid electrolyte containing Cl, where A can be selected from Li and Na, and M... α Optional from Zr and Hf, M β The choice of Ta and Nb indicates that the combination of tetravalent Zr / Hf metal centers with pentavalent Ta / Nb components has been disclosed to some extent in chloride solid electrolytes.
[0006] However, some halide solid electrolytes still have room for improvement in terms of room-temperature ionic conductivity, structural stability, and interfacial compatibility. To further regulate the local structure and ion migration environment of halide systems, existing technologies have begun to introduce oxygen anions to construct halide oxide solid electrolytes. Halide oxide solid electrolytes, with both halide and oxygen anions participating in the framework construction, can, to some extent, regulate the metal center coordination environment and lithium-ion migration channels, providing further controllability for the composition design of solid electrolytes. For example, CN118336096A discloses a halide oxide solid electrolyte and its preparation method, proposing the introduction of oxygen into various halide solid electrolytes and the controllability of the lithium-oxygen ratio. CN117878390B discloses a general formula Li 2a+b M b O a X' c X'' d The oxyhalide solid electrolyte is provided, where M can be selected from Ta, In or Zr, and X is a halogen. Specific examples of the composition of Ta-based oxyhalides are given.
[0007] As can be seen from the above disclosures, technologies such as halide solid electrolytes, heterovalent doping, and oxygen anion introduction have already established a certain foundation. However, existing schemes mostly focus on broad general formulas, parallel listing of elements, halogen composition adjustment, or general oxygen introduction routes; for those with Hf as the main metal center, Ta as the high-valence dopant component, and simultaneously containing Cl... - and O 2-For Li-Hf-Ta-Cl-O halide oxide systems with mixed anionic frameworks, current technologies still lack targeted material composition design and reproducible preparation schemes. Especially given the extensive research and publication on Zr-based halides and halide oxide systems, while Hf belongs to the same group as Zr and has similar chemical properties, the correlation between material composition, local coordination environment, and ion conductivity after Ta doping when Hf serves as the host metal center still lacks specific material system support. Therefore, it is still necessary to provide a tantalum-doped hafnium-based Li-Hf-Ta-Cl-O solid electrolyte material with a well-defined composition, a clear preparation route, and high room-temperature lithium-ion conductivity to expand the composition design and application basis of Hf-based halide oxide solid electrolytes.
[0008] Purpose of the invention The purpose of this invention is to provide a tantalum-doped hafnium-based halide oxide solid electrolyte that exhibits significantly improved ion conduction performance. When applied in all-solid-state lithium-ion batteries, it can significantly improve their air stability and long-cycle stability.
[0009] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A tantalum-doped hafnium-based halide oxide solid electrolyte, wherein the halide oxide solid electrolyte material contains Cl - With O 2- A lithium-ion conductor with a mixed anionic framework and containing high-valence metal Ta cation doping components, the chemical formula is: Li 2- x Hf 1-x Ta x Cl5O 0.5 Wherein, 0.25≤x≤0.75, and x is the mole fraction of Ta relative to the total amount of Hf and Ta metal cations.
[0010] In the tantalum-doped hafnium-based halide oxide solid electrolyte provided by this invention, based on the hafnium-based halide oxide framework, the metal site composition and local coordination environment are adjusted by Ta doping, thereby providing a suitable structural environment for lithium-ion migration. Specifically, Cl - With O 2- Together they participate in framework construction, forming a mixed anionic framework; the Ta cation doping component is Ta 5+ The form introduces and partially replaces Hf sites, forming a Li-Hf-Ta-Cl-O multi-element local coordination environment together with Li, Hf, Cl, and O. Through the above compositional design, the Hf-based halide oxide framework can structurally accommodate the compositional and local coordination changes introduced by Ta doping, thereby improving the lithium-ion migration environment and enhancing room-temperature ion conductivity.
[0011] The material described in this invention is not simply a replacement of the metal center in existing Zr-based halide oxide systems with Hf, but rather a Li-Hf-Ta-Cl-O halide oxide system with Hf as the main metal center, for which a clear compositional relationship and preparation scheme have been established. Although Hf and Zr both belong to Group IVB elements, the Hf-based halide oxide framework, when incorporating Ta... 5+ Subsequently, adaptive structural adjustments can be made to the compositional and local coordination changes caused by doping, thereby enabling the resulting material to exhibit high lithium-ion conductivity at room temperature.
[0012] The tantalum-doped hafnium-based halide oxide solid electrolyte material exhibits a conductivity of not less than 2.0 mS / cm at 25 °C. -1 The lithium-ion conductivity is high; and the tantalum-doped hafnium-based halide oxide solid electrolyte material contains both Hf and Ta, and the room temperature lithium-ion conductivity retention rate is not less than 50% after exposure in a dry atmosphere for 48 h.
[0013] Wherein, when the mole fraction x of Ta is 0.25, 0.5, or 0.75, the lithium-ion conductivity of the halide oxide solid electrolyte material at 25°C is not less than 2.5 mS / cm. -1 5.0 mS cm -1 10.0 mS cm -1 More preferably, when x is 0.5, the chemical formula of the tantalum-doped hafnium-based halide oxide solid electrolyte material is: Li 1.5 Hf 0.5 Ta 0.5 Cl5O 0.5 Furthermore, its lithium-ion conductivity at 25 °C is not less than 5.0 mS / cm. -1 .
[0014] The tantalum-doped hafnium-based halide oxide solid electrolyte material can be used as a solid electrolyte layer material in all-solid-state lithium-ion batteries, or as an ion conductor component in composite cathodes to improve lithium-ion transport within the cathode layer.
[0015] The present invention also provides a method for preparing a tantalum-doped hafnium-based halide oxide solid electrolyte, which is prepared by a mechanochemical solid-state reaction of a raw material system containing lithium source, oxygen source, hafnium source and tantalum source, without the need for a wet chemical route, and the obtained material does not undergo sintering or thermal annealing treatment.
[0016] The method for preparing tantalum-doped hafnium-based halide oxide solid electrolyte provided by this invention specifically includes: (1) Under an inert atmosphere, weigh Li₂O, LiCl, HfCl₄, and TaCl₅ according to the target chemical composition (Li₂O provides oxygen and part of the lithium source, LiCl provides lithium and chlorine sources, HfCl₄ provides hafnium and chlorine sources, and TaCl₅ provides tantalum and chlorine sources), wherein the target chemical composition is: Li 2-x Hf 1-x Ta x Cl5O 0.5 The molar ratio of Li₂O, LiCl, HfCl₄, and TaCl₅ satisfies the following condition: Li₂O : LiCl : HfCl₄ : TaCl 5= 0.5 : (1-x) : (1-x) : x; where 0.25 ≤ x ≤ 0.75; (2) The Li2O, LiCl, HfCl4 and TaCl5 are mixed and placed in a sealed ball mill container, and a mechanochemical solid-phase reaction is carried out under an inert atmosphere to obtain the tantalum-doped hafnium-based halide oxide solid electrolyte material; wherein the product obtained after ball milling is not subjected to sintering or hot annealing treatment.
[0017] In step (1), the inert atmosphere is an argon atmosphere or a nitrogen atmosphere, more preferably an argon atmosphere. The raw material weighing, mixing, canning, and sampling processes can be carried out in a glove box to reduce the possibility of HfCl4, TaCl5, and the resulting halide oxide solid electrolyte material coming into contact with air or moisture.
[0018] In step (2), the mechanochemical solid-phase reaction is carried out by high-energy mechanical ball milling, with a ball milling speed of 450-550 rpm and a ball milling time of 36-60 h; the high-energy mechanical ball milling is carried out by alternating cycles of forward rotation, intermittent, reverse rotation and intermittent rotation.
[0019] Preferably, the ball milling time is 48-60 h, the forward rotation time is 12 min, the interval after forward rotation is 6 min, the reverse rotation time is 12 min, and the interval after reverse rotation is 6 min.
[0020] In step (2), the sealed ball mill container is a zirconia-lined ball mill jar; the grinding beads are made of zirconia, the ball-to-material ratio is 80:1-120:1, and the diameter of the grinding beads includes at least two of 12 mm, 10 mm, 8 mm and 6 mm, so as to improve the mechanical energy transfer efficiency and the uniformity of raw material mixing.
[0021] After ball milling, the resulting product does not require sintering or thermal annealing and can be used as the tantalum-doped hafnium-based halide oxide solid electrolyte material for ionic conductivity testing, film pressing, or all-solid-state lithium-ion battery assembly.
[0022] In other alternative embodiments, the oxygen source may also include one or more of LiOH or Li2O2. When LiOH or Li2O2 is used to replace part or all of the oxygen source of Li2O, the amount of lithium source, oxygen source and metal chloride precursor added can be adjusted according to the stoichiometric relationship of Li, Hf, Ta, Cl and O in the target material so that the resulting material meets the composition requirements of the target halide oxide solid electrolyte.
[0023] The present invention also provides an application of the above-mentioned tantalum-doped hafnium halide oxide solid electrolyte or the tantalum-doped hafnium halide oxide solid electrolyte obtained by the above preparation method in an all-solid-state lithium-ion battery.
[0024] The present invention also provides an all-solid-state lithium-ion battery, comprising a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. The solid electrolyte layer comprises the tantalum-doped hafnium-based halide oxide solid electrolyte material. To improve the contact state between the layers within the battery (to improve the interface contact and ion transport continuity on the negative electrode side) and to reduce potential interfacial side reactions that may occur when the halide oxide solid electrolyte directly contacts the negative electrode metal material, a sulfide solid electrolyte interlayer is preferably provided between the solid electrolyte layer and the negative electrode layer. More preferably, the sulfide solid electrolyte interlayer comprises Li6PS5Cl.
[0025] In a preferred embodiment, the all-solid-state lithium-ion battery adopts a stacked structure, which sequentially includes a composite positive electrode layer, a solid electrolyte layer, a sulfide solid electrolyte intermediate layer, and a negative electrode side metal layer; wherein, the solid electrolyte layer includes a tantalum-doped hafnium halide solid electrolyte, and the sulfide solid electrolyte intermediate layer is disposed between the solid electrolyte layer and the negative electrode side metal layer.
[0026] Specifically, the composite positive electrode layer comprises a positive electrode active material, a tantalum-doped hafnium-based halide oxide solid electrolyte, and a conductive agent; the positive electrode active material includes NCM811, the chemical formula of which is LiNi. 0.8 Co 0.1 Mn 0.1 O2; the conductive agent includes one or more of vapor-grown carbon fiber (VGCF), Super P conductive carbon black, acetylene black, and carbon nanotubes; preferably, the mass ratio of NCM811, tantalum-doped hafnium halide solid electrolyte and vapor-grown carbon fiber is 6:3:1.
[0027] The composite cathode powder can be prepared by a dry mixing method, for example, by adding the above components in proportion to a mixing container and then subjecting it to high-speed vibratory ball milling to obtain a uniformly dispersed composite cathode powder. Preferably, the high-speed vibratory ball milling speed is 1200 rpm and the processing time is 1 min.
[0028] Optionally, the conductive agent may also be selected from Super P conductive carbon black (Super P), acetylene black, carbon nanotubes, or combinations thereof; the composite cathode powder may also be mixed by one or more of vibratory ball milling, planetary ball milling, grinding, or mechanical stirring. Preferably, the composite cathode powder is prepared by a solvent-free dry mixing method.
[0029] Specifically, the sulfide solid electrolyte interlayer comprises Li6PS5Cl, Li6PS5Br, and Li 10 GeP2S 12 One or more of the following; the negative electrode side metal layer includes a combination of an In metal layer and a lithium source layer, or includes a Li-In pre-alloy layer; wherein the lithium source layer includes one or more of metallic lithium, LiCu, and Li-In pre-alloy.
[0030] In one specific embodiment, the all-solid-state lithium-ion battery is assembled using an in-mold layer-by-layer pressing method. Preferably, a 10 mm diameter pressing mold with ceramic bushings is used for layer-by-layer pressing to improve the contact consistency between functional layers and reduce the risk of edge short circuits.
[0031] The method for fabricating the all-solid-state lithium-ion battery employs an in-mold layer-by-layer pressing assembly, including: (1) Add tantalum-doped hafnium-based halide oxide solid electrolyte to a tablet mold with a ceramic bushing and press it to form a solid electrolyte layer; (2) Sulfide solid electrolyte intermediate layer powder is added to one side of the solid electrolyte layer and compacted to form a sulfide solid electrolyte intermediate layer; (3) Add composite cathode powder to the side of the solid electrolyte layer away from the sulfide solid electrolyte intermediate layer and compact it to form a composite cathode layer; (4) A negative electrode metal layer is provided on the side of the sulfide solid electrolyte intermediate layer away from the solid electrolyte layer, and then compressed and sealed.
[0032] The ceramic bushing is an alumina ceramic bushing, a zirconia ceramic bushing, or other insulating ceramic bushing; the amount of the halide oxide solid electrolyte material is 70-90 mg, and it is pressed under an axial load of 0.5-2 t for a holding time of 0.5-5 min; the amount of the sulfide solid electrolyte intermediate layer powder is 40-60 mg, the pressing load is 1-3 t for a holding time of 0.5-5 min; the amount of the composite positive electrode powder is 7-10 mg, and it is again subjected to an axial load of 0.5-2 t for a holding time of 0.5-5 min. The inner diameter of the tableting mold is 10 mm; the negative electrode side metal layer includes any of the following structures: (1) In metal foil and LiCu metal sheet are bonded together in sequence, wherein the thickness of the In metal foil is 5-50 μm and the thickness of the LiCu metal sheet is 5-100 μm; (2) Pre-fabricated Li-In alloy layer; A negative electrode-side metal layer is disposed on the outer side of the sulfide solid electrolyte intermediate layer. Preferably, the negative electrode-side metal layer comprises an indium metal foil and a LiCu metal sheet sequentially bonded together. The thickness of the indium metal foil is preferably 20 μm, and the thickness of the LiCu metal sheet is preferably 10 μm. The indium metal foil is used to form a Li-In alloying interface with the lithium source during battery assembly and subsequent pressing, thereby improving the stability and repeatability of the negative electrode-side interface. The LiCu metal sheet serves as a lithium source layer and a composite current collector layer, providing the lithium source and assisting in the formation of a uniform negative electrode-side contact interface. Optionally, the thickness of the indium metal foil is 5-50 μm; the lithium source layer can be selected from lithium metal, LiCu, Li-In pre-alloy, or a combination thereof, with a thickness of 5-100 μm.
[0033] After completing the above-described stacked structure, the resulting battery structure is installed into a battery casing or test mold for compression encapsulation. Preferably, a torque wrench is used to apply a stable torque to improve the assembly consistency between different batteries. The encapsulation torque is preferably 20 Nm. After encapsulation, a pressure holding process can be performed under compression to promote the formation of a stable alloying interface between the indium layer and the lithium source layer and reduce the initial interface resistance. When the negative electrode side metal layer uses an indium metal layer to form a Li-In alloying interface in situ with the lithium source layer, it is preferable to hold the pressure under compression for 12 hours after encapsulation; alternatively, the in-situ alloying pressure holding time is 12-24 hours. When the negative electrode side metal layer directly uses a pre-fabricated Li-In alloy layer, it can be tested or used after holding the pressure under compression for 2 hours after encapsulation.
[0034] Through the above-described layer-by-layer pressing and negative electrode side interface construction methods, an all-solid-state lithium-ion battery containing the tantalum-doped hafnium-based halide oxide solid electrolyte material provided by this invention can be obtained.
[0035] The all-solid-state lithium-ion battery provided by this invention retains no less than 90% of its capacity after 300 cycles at 25 °C and 0.5 C.
[0036] Compared with the prior art, the present invention has at least the following beneficial effects: (1) Through Ta 5+ Modulating the Hf-based Cl / O mixed anion framework to improve lithium-ion conductivity This invention is based on hafnium-based halide oxides, in Cl - With O 2- Introducing high-valence Ta into the mixed anionic framework formed by the two 5+ Doping components make Ta 5+ Partial substitution of Hf sites modulates the composition of the metal cation sites and their surrounding local coordination environment. This compositional design improves the lithium-ion migration environment and enhances the room-temperature lithium-ion conductivity of the material. Compared to undoped Li₂HfCl₅O₂... 0.5 The tantalum-doped hafnium-based halide oxide solid electrolyte material described in this invention exhibits significantly improved ion conductivity.
[0037] (2) Expanding the compositional design of Hf-based halide oxide solid electrolytes Among existing halide and halide oxide solid electrolytes, Zr-based systems have been extensively studied and publicly disclosed, while the specific composition design, doping control, and performance verification of Hf-based halide oxide systems remain relatively insufficient. This invention uses Hf as the host metal center and introduces Ta into a Cl / O mixed anionic framework. 5+ The doping components enable the Hf-based framework to adaptively accommodate changes in metal sites and local coordination caused by Ta doping. The resulting halide oxide solid electrolyte materials exhibit well-defined compositional relationships and high room-temperature lithium-ion conductivity, expanding the material design space for Hf-based hybrid anion solid electrolytes.
[0038] (3) Balancing process simplification with solid electrolyte application performance This invention prepares tantalum-doped hafnium halide oxide solid electrolyte materials via a mechanochemical solid-state reaction, avoiding problems such as solvent residue, hydrolysis side reactions, and complex post-processing associated with wet chemical routes. It also avoids the high energy consumption and process control difficulties associated with sintering or thermal annealing processes. The resulting material exhibits high room-temperature lithium-ion conductivity without high-temperature post-treatment and can be used for solid electrolyte lamination, composite cathode fabrication, and all-solid-state lithium-ion battery assembly. Therefore, this invention simplifies the preparation process while maintaining the material's practical applicability as a solid electrolyte.
[0039] (4) Introducing Hf to construct an Hf / Ta solid solution, which maintains high ionic conductivity while also exhibiting excellent air stability and long-term cycling stability. Existing halide oxide solid electrolyte technologies mostly use single high-valence metal (such as Ta, Nb) halide oxides as the optimal solution, and it is believed that introducing a second metal into this system will reduce ionic conductivity, thus leading the field towards pure tantalum or pure niobium compositions. This invention uses hafnium-based halide oxides as the framework, introducing Ta to form Li. 2-x Hf 1-x Ta x Cl5O 0.5 A solid solution of Hf / Ta coexisting (0.25 ≤ x ≤ 0.75). Compared with pure tantalum endmembers without Hf (x=1), the Hf-containing material of this invention has a slightly lower room temperature lithium-ion conductivity (but is still not lower than 2.0 mS / cm). -1 When x=0.5, it is approximately 5.22 mS / cm. -1 However, its air stability and long-cycle stability of all-solid-state lithium-ion batteries are significantly improved: after the Hf-containing material is exposed to a dry atmosphere for 48 h, the ionic impedance only increases slowly and the conductivity retention rate is not less than 50%. The assembled all-solid-state lithium-ion battery retains 95.73% of its capacity after 300 cycles at 0.5 C. In contrast, the pure tantalum end-member exhibits significant performance degradation during air exposure and long-cycle operation. Under the same conditions, the capacity of the all-solid-state battery decreases significantly to about 15 mAh g⁻¹ after 300 cycles. -1 The above results contradict the technical implication of the prior art that "the single high-valence metal system has the best ionic conductivity," indicating that introducing Ta into the hafnium-based framework to construct an Hf / Ta solid solution can bring unexpected improvements in air stability and cycling stability while maintaining high room temperature ionic conductivity. Attached Figure Description
[0040] Figure 1 Scanning electron microscope images and magnified views of LHCO and Ta-LHCO show particle morphology and size distribution, with scale bars of 5 μm and 500 nm, respectively. Figure 2 The image shows a scanning electron microscope image of Ta-LHCO and surface distribution diagrams of Ta, Hf, Cl, and O elements. The scale bar is 5 μm, showing the uniform distribution of each element in the particle region. Figure 3 X-ray diffraction patterns of LHCO and Ta-LHCO and the positions of relevant standard diffraction peaks; Figure 4 High-resolution transmission electron microscope images and selected area electron diffraction patterns of LHCO and Ta-LHCO, scale bars are 2 nm (HR-TEM) and 10 nm-1 (SAED). Figure 5O 1s X-ray photoelectron spectra and peak separation results of LHCO and Ta-LHCO; Figure 6 Solids of LHCO3 and Ta-LHCO3 7 Li NMR spectrum; Figure 7 The room temperature AC impedance spectra of LHCO3 and Ta-LHCO3 are shown. Figure 8 The DC polarization current response curves and electronic conductivity fitting plots of LHCO and Ta-LHCO under different applied voltages are shown. Figure 9 The room temperature AC impedance spectra of samples with different Ta contents and the relationship between lithium-ion conductivity and lithium-ion migration activation energy as x are shown. Figure 10 The charge-discharge cycle performance and coulombic efficiency of the Ta-LHCO-based all-solid-state lithium-ion battery at 0.5 C were evaluated. Figure 11 The discharge specific capacity-cycle curves and charge-discharge curves of Ta-LHCO-based all-solid-state lithium-ion batteries at different rates are shown. Figure 12 The table shows the room temperature AC impedance spectra of Ta-LHCO (x=0.5) obtained in Example 1 after exposure to a dry atmosphere for different times (0.5 h, 12 h, 24 h, 48 h). Figure 13 The discharge specific capacity-cycle curves and coulombic efficiency of an all-solid-state lithium-ion battery (NCM811|LTCO|Li6PS5Cl|Li-In) based on pure tantalum end-member LTCO (x=1) at room temperature (25 °C) and 0.5 C are presented. Detailed Implementation
[0041] Example 1: Tantalum-doped hafnium-based halide oxide solid electrolyte (Ta-LHCO, x=0.5) This embodiment provides a method for preparing a tantalum-doped hafnium-based halide oxide solid electrolyte material. This method can obtain an electrolyte material that can be directly used in all-solid-state lithium-ion batteries without sintering or high-temperature heat treatment.
[0042] Raw materials were weighed under an inert atmosphere (preferably argon) and prepared according to a molar ratio of Li₂O:LiCl:HfCl₄:TaCl₅ = 0.5:0.5:0.5:0.5 (x = 0.5). LiCl served as the lithium source; Li₂O as the oxygen source; and HfCl₄ and TaCl₅ as metal halide precursors.
[0043] The above raw materials were placed into a 100 mL sealed ball mill jar made of zirconia and subjected to high-energy ball milling under an inert atmosphere. The ball-to-material ratio was 80:1-120:1; the milling speed was 450-550 rpm; and the milling time was 36-60 h. The milling process employed a cyclic pattern of 12 min forward rotation, 6 min interval, 12 min reverse rotation, and 6 min interval. After milling, the resulting powder was removed, yielding a product with the chemical composition Li. 1.5 Hf 0.5 Ta 0.5 Cl5O 0.5 The tantalum-doped hafnium-based halide oxide solid electrolyte material is denoted as Ta-LHCO.
[0044] After the above-mentioned mechanochemical solid-state reaction treatment, the raw materials undergo thorough mixing and solid-state reaction under the action of mechanical energy to obtain the target tantalum-doped hafnium-based halide oxide solid electrolyte powder. The obtained powder can be used for subsequent pressing, structural characterization, electrochemical performance testing, and all-solid-state lithium-ion battery assembly without sintering or high-temperature thermal annealing.
[0045] Comparative Example 1: Preparation of Undoped Hafnium-based Halogen Oxide Solid Electrolyte Materials To evaluate the effect of Ta doping on the ion conductivity of hafnium-based halide oxide solid electrolyte materials, this comparative example prepared undoped hafnium-based halide oxide solid electrolyte material Li₂HfCl₅O without the addition of TaCl₅. 0.5 , denoted as LHCO.
[0046] Specifically, under an inert atmosphere (preferably argon), raw materials were weighed according to a molar ratio of Li₂O:LiCl:HfCl₄ = 0.5:1:1. These raw materials were then placed together in a sealed ball mill jar made of zirconia and ball-milled according to the mechanochemical solid-state reaction conditions described in Example 1. After ball milling, the resulting powder was removed, yielding the undoped hafnium-based halide oxide solid electrolyte material LHCO. The obtained material was not subjected to sintering or high-temperature annealing and was used as a comparative sample for subsequent structural characterization and performance comparison with the Ta-LHCO material obtained in Example 1.
[0047] Test Example 1: Structural characterization and ion conductivity testing of the materials obtained in Example 1 and Comparative Example 1. To evaluate the effect of Ta doping on the structure and ion conduction performance of hafnium-based halide oxide solid electrolyte materials, the Ta-LHCO obtained in Example 1 and the LHCO obtained in Comparative Example 1 were subjected to scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), solid-state nuclear magnetic resonance (ssNMR), electrochemical impedance spectroscopy (EIS), temperature-dependent conductivity and direct current polarization (DC).
[0048] SEM results (e.g.) Figure 1 The results showed that both LHCO and Ta-LHCO were mainly composed of aggregated micron-sized particles with irregular blocky or plate-like morphologies. EDS elemental distribution measurements were performed on selected regions of Ta-LHCO (e.g.,...). Figure 2 The results showed that Ta, Hf, Cl, and O were all detectable within the test area, and no obvious elemental segregation was observed. This indicates that under the mechanochemical solid-state reaction conditions described in this embodiment, Ta, Hf, Cl, and O exhibit good distribution consistency within the selected micro-region. It should be noted that the EDS results primarily reflect the elemental distribution at the micrometer scale and should not be used as the sole criterion for determining uniform doping at the atomic scale.
[0049] XRD test results show (e.g.) Figure 3 The main diffraction peaks of Ta-LHCO and LHCO are basically in the same position, indicating that they retain similar main phase structures and have similar main diffraction characteristics. Compared with LHCO, the main diffraction peaks of Ta-LHCO generally show a slight shift towards higher angles. According to Bragg's equation, the shift of diffraction peaks towards higher angles usually corresponds to a decrease in the corresponding average interplanar spacing, indicating that the average lattice parameters or local structural environment of the material are adjusted to some extent after the introduction of Ta. Since XRD reflects the average structural information of the material, the above peak position changes are used to illustrate the difference in structural characteristics before and after Ta doping, rather than as direct evidence of the lithium-ion migration mechanism.
[0050] TEM and SAED test results (e.g.) Figure 4 The results show that lattice fringes and diffraction rings are observed in both LHCO and Ta-LHCO. In HRTEM images, the interplanar spacing of the (0 4 1) crystal plane in LHCO is approximately 0.281 nm, while that in Ta-LHCO is approximately 0.287 nm. SAED patterns show that the two materials have similar diffraction ring distributions, with slight variations in the positions of some diffraction rings in Ta-LHCO. These results indicate that the introduction of Ta causes observable changes in the local interplanar spacing and diffraction characteristics of the materials, while the overall structural features remain similar to the undoped sample.
[0051] XPS O 1s test results (e.g.) Figure 5 The results show that the ratio of non-bridging oxygen to bridging oxygen in LHCO is approximately 0.21, while the ratio in Ta-LHCO is approximately 0.24. The small difference in the non-bridging oxygen / bridging oxygen ratio indicates that Ta doping alters the oxygen species environment in Hf-based halide oxides, but does not exhibit significant oxygen network depolymerization. This result is consistent with the design concept of this invention: "introducing Ta doping to regulate the structure while maintaining the basic characteristics of the Cl / O mixed anion framework."
[0052] solid 7 Li NMR test results (e.g.) Figure 6 The data shows that LHCO's 7 The chemical shift of Li is approximately -0.80 ppm, and that of Ta-LHCO3 is... 7 The chemical shift of Li is approximately -0.65 ppm. Compared to the undoped sample, Ta-LHCO3 exhibits... 7 The Li resonance peak shifted by approximately 0.15 ppm, indicating that the local chemical environment surrounding Li changed after Ta doping. This result demonstrates that the introduction of Ta can affect the local coordination environment of lithium ions.
[0053] LHCO and Ta-LHCO were respectively pressed into electrolyte sheets and then subjected to AC impedance testing. The test results (e.g.) Figure 7 The results show that the lithium-ion conductivity of LHCO at room temperature is approximately 0.46 mS / cm. -1 The lithium-ion conductivity of Ta-LHCO at room temperature is approximately 5.22 mS / cm. -1 Compared with undoped LHCO, Ta-LHCO exhibits significantly improved room-temperature lithium-ion conductivity, indicating that Ta doping can effectively reduce the ion conduction impedance of hafnium-based halide oxide solid electrolytes.
[0054] Further temperature-dependent conductivity tests were conducted, and the activation energy for lithium-ion migration was fitted using the Arrhenius relation. The results showed that the activation energy for lithium-ion migration of LHCO was approximately 0.371 eV, while that of Ta-LHCO was approximately 0.248 eV. These results indicate that under the test conditions, Ta-LHCO exhibits a lower activation energy for lithium-ion migration than LHCO, corresponding to its higher room-temperature lithium-ion conductivity.
[0055] DC polarization testing is used to evaluate the electronic conductance contribution of a sample. Test results (e.g.) Figure 8 The results show that the electronic conductivity of Ta-LHCO at room temperature is approximately 1.17 × 10⁻⁶. -8 mS cm -1 The electronic conductivity of LHCO3 at room temperature is approximately 1.99 × 10⁻⁶.-8 mS cm -1 The electronic conductivity values mentioned above are much lower than the room-temperature ionic conductivity of the corresponding samples, indicating that the total conductivity of LHCO and Ta-LHCO mainly comes from lithium-ion conduction, with electronic conduction contributing relatively little.
[0056] The above test results show that, under the same mechanochemical preparation conditions, the introduction of Ta doping components can improve the ion conduction performance of hafnium-based halide oxide solid electrolyte materials while maintaining their ion conductor characteristics as solid electrolyte materials.
[0057] Example 2: Preparation of tantalum-doped hafnium halide solid electrolyte materials with different Ta contents This embodiment, based on Example 1, prepares materials with different Ta contents by adjusting the molar ratio of TaCl5 to HfCl4 to study the effect of Ta doping content on the ionic conductivity of the materials. Specifically, the target chemical formula is: Li 2-x Hf 1-x Ta x Cl5O 0.5 x = 0.25, 0.50, 0.75; Except for the relative amounts of raw materials, all other preparation conditions followed exactly as in Example 1, i.e., high-energy ball milling was performed under an inert atmosphere without high-temperature sintering or annealing. The resulting samples were used for subsequent ionic conductivity and activation energy testing.
[0058] Test Example 2: Ion Conductivity Test of Samples with Different Ta Contents To evaluate the effect of Ta content on the ion conductivity of hafnium-based halide oxide solid electrolyte materials, AC impedance and temperature-dependent conductivity tests were performed on samples with different Ta contents obtained in Example 2. The test samples included undoped LHCO from Comparative Example 1, samples with x=0.25 and x=0.75 from Example 2, and a sample with x=0.50 from Example 1. To further observe the conductivity change trend after increasing Ta content, a Ta end-member reference sample with x=1 was prepared for comparison testing; this reference sample is not considered a preferred protection target for the hafnium-based tantalum doped material of this invention.
[0059] Each sample powder was pressed into an electrolyte sheet, and AC impedance was tested under the same test conditions. For example... Figure 9 As shown, within the range of 0.25 ≤ x ≤ 0.75, the room temperature lithium-ion conductivity of the sample increases from 2.65 mS / cm with increasing Ta content. -1 Increased to 10.78 mS cm -1 Both were significantly higher than the 0.46 mS / cm of undoped LHCO. -1The results indicate that, under the same mechanochemical preparation conditions, the introduction of the Ta component can effectively reduce the ion conduction impedance of hafnium-based halide oxide solid electrolytes and improve the room-temperature lithium-ion conductivity.
[0060] Temperature-dependent conductivity tests were performed on each sample, and the activation energy for lithium-ion migration was calculated using the Arrhenius relation. Figure 9 As shown, the activation energy of undoped LHCO is approximately 0.371 eV; when x = 0.25, 0.50, and 0.75, the activation energy decreases to approximately 0.293 eV, 0.248 eV, and 0.225 eV, respectively. This result indicates that the activation energy for lithium-ion migration decreases after Ta doping, which is consistent with the increase in room temperature conductivity.
[0061] The data from x=0.25 to x=0.75 show that increasing the Ta content continuously improves the ion conductivity of the material. While the Ta-terminal reference sample with x=1 exhibits slightly higher room-temperature lithium-ion conductivity and slightly lower activation energy, its air stability and long-cycle stability in all-solid-state lithium-ion batteries are significantly inferior to the Hf / Ta solid solution containing Hf (see Comparative Example 2 and Test Example 4). Furthermore, this sample no longer contains Hf and is not within the preferred composition range of tantalum-doped hafnium-based halide oxides in this invention. Therefore, this invention uses 0.25≤x≤0.75 as the main composition range for tantalum-doped hafnium-based halide oxide solid electrolyte materials, where x=0.50 is a specific value for Li. 1.5 Hf 0.5 Ta 0.5 Cl5O 0.5 As a representative implementation, it possesses both a well-defined Hf / Ta coexistence structure and high room-temperature lithium-ion conductivity.
[0062] In summary, the EIS and Arrhenius test results of samples with different Ta contents show that the introduction of Ta can significantly improve the room temperature lithium-ion conductivity of hafnium-based halide oxide solid electrolyte materials and reduce the lithium-ion migration activation energy. Within the Hf / Ta coexistence composition range defined in this invention, the obtained materials all exhibit superior ion conductivity compared to undoped LHCO.
[0063] Example 3: Fabrication of an all-solid-state lithium-ion battery based on Ta-LHCO This embodiment uses the tantalum-doped hafnium-based halide oxide solid electrolyte material Ta-LHCO obtained in Example 1 to assemble an all-solid-state lithium-ion battery to evaluate the application performance of this material in a practical solid-state battery system. The battery structure is NCM811|Ta-LHCO|Li6PS5Cl|Li-In, where NCM811 is LiNi. 0.8 Co 0.1 Mn 0.1O2 and Ta-LHCO serve as the ionic conductor components in the halide oxide solid electrolyte layer and composite positive electrode, Li6PS5Cl serves as the intermediate layer of the sulfide solid electrolyte on the negative electrode side, and Li-In serves as the alloy interface on the negative electrode side.
[0064] Specifically, the Ta-LHCO powder obtained in Example 1 was first weighed and placed in a 10 mm diameter tableting mold with a ceramic bushing. An axial load was applied to press it into a solid electrolyte layer. Subsequently, Li6PS5Cl sulfide solid electrolyte powder was added to one side of the solid electrolyte layer as an intermediate layer and compacted to improve the interfacial contact between the halide oxide solid electrolyte and the negative electrode metal layer.
[0065] The composite cathode powder consists of NCM811 cathode active material, Ta-LHCO solid electrolyte, and vapor-grown carbon fiber (VGCF) in a mass ratio of 6:3:1. The above components are dry-mixed to obtain the composite cathode powder, which is then added to the side of the solid electrolyte layer away from the Li6PS5Cl interlayer. An axial load is then applied for compaction, ensuring a tight contact between the composite cathode layer and the Ta-LHCO solid electrolyte layer.
[0066] A negative electrode metal layer is disposed on the outer side of the Li6PS5Cl intermediate layer. The negative electrode metal layer can be formed by in-situ contact between indium metal foil and lithium-containing metal layer to form a Li-In alloy interface, or a pre-fabricated Li-In alloy layer can be used directly. When the in-situ Li-In alloy interface is formed between indium metal foil and lithium source layer, electrochemical testing is performed after the battery is sealed and held under pressure for 12 hours; when a pre-fabricated Li-In alloy layer is used directly, electrochemical testing is performed after the battery is sealed and held under pressure for 2 hours.
[0067] The obtained all-solid-state lithium-ion battery was subjected to electrochemical performance testing at room temperature (25 °C). The charge / discharge voltage window was 2.8–4.3 V (vs. Li). + / Li), the corresponding test voltage window for the Li-In anode system can be converted according to the Li-In reference potential. Based on the NCM811 cathode active material, the nominal specific capacity is calculated at 180 mAh g. -1 calculate.
[0068] Test Example 3: Electrochemical Performance Testing of All-Solid-State Lithium-ion Batteries Based on Ta-LHCO An all-solid-state lithium-ion battery, NCM811|Ta-LHCO|Li6PS5Cl|Li-In, assembled using the Ta-LHCO tantalum-doped hafnium-based halide oxide solid electrolyte material obtained in Example 1, was tested for cycle performance and rate performance at room temperature (25 °C). The battery test voltage range was set to correspond to the operating voltage range of the NCM811 cathode.
[0069] The battery was first activated for two cycles at a current density of 0.1 C, and then subjected to long-cycle testing at 0.5 C. The results showed ( Figure 10 In the initial stage of cycling, the battery's discharge specific capacity is approximately 85 mAh g. -1 It then gradually stabilized and remained at 95 mAhg -1 The capacity retention rate was approximately 95.73% after 300 cycles, and the coulombic efficiency was close to 100% during the cycle. This demonstrates that the all-solid-state lithium-ion battery constructed using Ta-LHCO as the halide oxide solid electrolyte material, combined with a sulfide solid electrolyte interlayer and a Li-In anode interface, can achieve good cycle stability and reusability without the need for high-temperature sintering or annealing.
[0070] In the rate performance test, the battery was charged and discharged sequentially at 0.1 C, 0.3 C, 0.5 C, 1 C, and 2 C, and then returned to 0.3 C. The test results show ( Figure 11 The battery's discharge specific capacity at 0.1 C is approximately 160-168 mAh g. -1 0.3 C approximately 120-125 mAh g -1 0.5 C approximately 90-95 mAh·g -1 1 C is approximately 40 mAh g -1 2 C approximately 20 mAhg -1 After the rate is restored to 0.3 C, the discharge capacity can recover to approximately 120 mAh g. -1 It decays slowly in subsequent cycles but still remains at 105 mAh g⁻¹. -1 The coulombic efficiency remained within the range of 95-100% throughout the rate switching process. This indicates that the all-solid-state lithium-ion battery can continuously perform charge-discharge processes at different rates and possesses a certain degree of rate adaptability and capacity recovery capability.
[0071] In summary, the NCM811|Ta-LHCO|Li6PS5Cl|Li-In all-solid-state lithium-ion battery shown in Example 3 exhibits good cycle stability and rate response at room temperature. Experimental results demonstrate that the Ta-LHCO solid electrolyte material not only maintains high room-temperature lithium-ion conductivity but also serves as a solid electrolyte layer and composite cathode ion conductor component in practical all-solid-state lithium-ion batteries, achieving relatively stable and reversible electrochemical performance.
[0072] Comparative Example 2: Preparation of pure tantalum end-member halide oxide solid electrolyte material (x=1) To evaluate the effect of Hf on the air stability of tantalum-doped hafnium halide oxide solid electrolyte materials and the long-cycle stability of all-solid-state lithium-ion batteries, a comparative example of a pure tantalum end-member hafnium halide oxide solid electrolyte material (x=1), denoted as LTCO, was prepared. Under an inert atmosphere (preferably argon), the raw materials (i.e., Li₂O:TaCl₅ = 0.5:1 molar ratio) were weighed... 2-x Hf 1-x Ta x Cl5O 0.5 In the formula x=1, the corresponding chemical formula is LiTaCl5O 0.5 The remaining ball milling conditions were the same as in Example 1. The product obtained was not subjected to sintering or high-temperature heat annealing treatment, and thus a pure tantalum end-member halide oxide solid electrolyte material LTCO was obtained. This material was used as a comparative sample to compare the air stability and long-cycle stability with the Hf / Ta solid solution containing Hf of the present invention.
[0073] Test Example 4: Comparison of air stability and long-cycle stability of Hf-containing samples and pure tantalum end-members (LTCO) batteries. Air stability test: The Ta-LHCO3 (x=0.5) obtained in Example 1 was placed in a dry atmosphere and exposed for 0.5 h, 12 h, 24 h, and 48 h, respectively, before being pressed into electrolyte sheets and subjected to room temperature AC impedance testing. Results (e.g.) Figure 12 The results showed that as the exposure time increased, the bulk and interfacial impedance of Ta-LHCO increased only slowly. After 48 h of exposure, the impedance remained at a low level, corresponding to a room temperature lithium-ion conductivity retention rate of no less than 50%, indicating that Ta-LHCO containing Hf has good air stability.
[0074] Long-cycle comparison of all-solid-state batteries: Using the pure tantalum end-member LTCO obtained in Comparative Example 2 as the solid electrolyte, an NCM811|LTCO|Li6PS5Cl|Li-In all-solid-state lithium-ion battery was assembled in the same manner as in Example 3, and long-cycle tests were conducted at room temperature (25°C) and 0.5°C. Results (e.g.) Figure 13 The data shows that the first-cycle discharge specific capacity of this pure tantalum end-cell battery is approximately 137 mAh g.-1 However, the capacity decays rapidly with cycling, and after 300 cycles, the discharge specific capacity drops to approximately 15 mAh g. -1 The capacity retention rate was only about 11%. In contrast, the NCM811|Ta-LHCO|Li6PS5Cl|Li-In battery (a solid solution containing Hf with x=0.5) obtained in Example 3 achieved a capacity retention rate of 95.73% after 300 cycles under the same conditions (see Test Example 3 and...). Figure 10 ).
[0075] The above comparison shows that although the pure tantalum end-member (x=1) has a slightly higher room-temperature lithium-ion conductivity, its air stability and long-term cycle stability in all-solid-state lithium-ion batteries are significantly inferior to those of the Hf / Ta solid solution containing Hf. Introducing Ta into the hafnium-based framework while retaining Hf (0.25≤x≤0.75) can achieve significantly better air stability and long-term cycle stability while maintaining a high room-temperature lithium-ion conductivity. This overcomes the technical bias in existing technologies that "single high-valence metal halide oxide systems have the best performance" and produces unexpected technical effects.
Claims
1. A tantalum-doped hafnium-based halide oxide solid electrolyte, characterized in that, The halide oxide solid electrolyte material contains Cl - With O 2- A lithium-ion conductor with a mixed anionic framework and containing high-valence metal Ta cation doping components, the chemical formula is: Li 2-x Hf 1-x Ta x Cl5O 0.5 Where 0.25≤x≤0.75, and x is the mole fraction of Ta relative to the total amount of Hf and Ta metal cations.
2. The tantalum-doped hafnium-based halide oxide solid electrolyte according to claim 1, characterized in that, The tantalum-doped hafnium-based halide oxide solid electrolyte material exhibits a conductivity of not less than 2.0 mS / cm at 25 °C. -1 The lithium-ion conductivity is high; and the room-temperature lithium-ion conductivity of the tantalum-doped hafnium-based halide solid electrolyte material is not less than 50% after being exposed to a dry atmosphere for 48 hours.
3. A method for preparing a tantalum-doped hafnium-based halide oxide solid electrolyte, characterized in that, include: (1) Under an inert atmosphere, according to the target chemical composition Li 2-x Hf 1-x Ta x Cl5O 0.5 Weigh out Li₂O, LiCl, HfCl₄ and TaCl₅, wherein the molar ratio of Li₂O, LiCl, HfCl₄ and TaCl₅ satisfies: Li₂O:LiCl:HfCl₄:TaCl₅=0.5:(1-x):(1-x):x, 0.25≤x≤0.75; (2) The Li2O, LiCl, HfCl4 and TaCl5 are mixed and placed in a sealed ball mill container, and a mechanochemical solid-phase reaction is carried out under an inert atmosphere to obtain the tantalum-doped hafnium-based halide oxide solid electrolyte material; wherein the product obtained after ball milling is not subjected to sintering or hot annealing treatment.
4. The method for preparing tantalum-doped hafnium-based halide oxide solid electrolyte according to claim 3, characterized in that, In step (2), the mechanochemical solid-phase reaction is carried out by high-energy mechanical ball milling, with a ball milling speed of 450-550 rpm and a ball milling time of 36-60 h; the high-energy mechanical ball milling is carried out by alternating cycles of forward rotation, intermittent, reverse rotation and intermittent rotation.
5. The method for preparing tantalum-doped hafnium-based halide oxide solid electrolyte according to claim 3, characterized in that, In step (2), the sealed ball mill container is a zirconia-lined ball mill jar; the grinding beads are made of zirconia, the ball-to-material ratio is 80:1-120:1, and the diameter of the grinding beads includes at least two of 12 mm, 10 mm, 8 mm and 6 mm.
6. The application of the tantalum-doped hafnium halide solid electrolyte according to any one of claims 1-2 or the tantalum-doped hafnium halide solid electrolyte obtained by the preparation method according to any one of claims 3-5 in an all-solid-state lithium-ion battery.
7. The application according to claim 6, characterized in that, The all-solid-state lithium-ion battery includes a composite positive electrode layer, a solid electrolyte layer, a sulfide solid electrolyte intermediate layer, and a negative electrode side metal layer; wherein, the solid electrolyte layer includes a tantalum-doped hafnium halide solid electrolyte, and the sulfide solid electrolyte intermediate layer is disposed between the solid electrolyte layer and the negative electrode side metal layer.
8. The application according to claim 6, characterized in that, The method for fabricating the all-solid-state lithium-ion battery employs an in-mold layer-by-layer pressing assembly, including: (1) Add tantalum-doped hafnium-based halide oxide solid electrolyte into a tablet mold with a ceramic bushing and press it to form a solid electrolyte layer; (2) Sulfide solid electrolyte intermediate layer powder is added to one side of the solid electrolyte layer and compacted to form a sulfide solid electrolyte intermediate layer; (3) Add composite cathode powder to the side of the solid electrolyte layer away from the sulfide solid electrolyte intermediate layer and compact it to form a composite cathode layer; (4) A negative electrode metal layer is provided on the side of the sulfide solid electrolyte intermediate layer away from the solid electrolyte layer, and then compressed and sealed.
9. The application according to claim 8, characterized in that, The ceramic bushing is an insulating ceramic bushing, selected from alumina ceramic bushings or zirconium oxide ceramic bushings; the amount of tantalum-doped hafnium-based halide oxide solid electrolyte is 70-90 mg, the pressing load is 0.5-2 t, and the holding time is 0.5-5 min; the amount of sulfide solid electrolyte intermediate layer powder is 40-60 mg, the pressing load is 1-3 t, and the holding time is 0.5-5 min; the amount of composite cathode powder is 7-10 mg, the pressing load is 0.5-2 t, and the holding time is 0.5-5 min.
10. The application according to claim 6, characterized in that, The all-solid-state lithium-ion battery retains no less than 90% of its capacity after 300 cycles at 25 °C and 0.5 C.
Citation Information
Patent Citations
Halogen solid electrolyte materials and batteries using these materials
CN112204675B
Oxyhalide solid electrolyte and preparation method thereof, and battery
CN117878390B
Solid electrolyte and battery
CN119487582A